Treatment of acromioclavicular dislocation of the shoulder in adults - press review - Bartlomiej Wojcik; Kinga Świąder; Kalina van der Bend; Agata Lis (Kazimierz Wielki University, 2023)
Introduction:  Acromioclavicular joint dislocation is one of the most common shoulder injuries treated in a sport‐active population. In this article we reviewed the epidemiology, symptoms, and various surgical techniques for the treatment of acromioclavicular dislocation. Material and methods: The work was based on medical articles collected in PubMed, websites and medical books. The research was conducted by looking at keywords such as: "acromioclaviculal dislocation", "treatment of acromioclaviculal dislocation ". Results: There are many methods of treating acromioclaviculal dislocation, ranging from conservative treatment to surgical treatment. Conclusions: Treating acute and chronic ACJ injuries is still a challenging task.The myriad of existing techniques is indicative for the uncertainty regarding this topic and a gold standard has not yet been determined. However, when diagnosed correctly and treated accordingly, results are overall satisfactory.